Answer: -4, -3, -2
Step-by-step explanation:
By inspection, we know
is a root.
We can thus rewrite the equation as
![(x+2)\left(\frac{x^3 + 9x^2 + 26x+24}{x+2} \right)=0\\\\(x+2)(x^2 + 7x+12)=0\\\\(x+2)(x+3)(x+4)=0\\\\x=-4, -3, -2](https://tex.z-dn.net/?f=%28x%2B2%29%5Cleft%28%5Cfrac%7Bx%5E3%20%2B%209x%5E2%20%2B%2026x%2B24%7D%7Bx%2B2%7D%20%5Cright%29%3D0%5C%5C%5C%5C%28x%2B2%29%28x%5E2%20%2B%207x%2B12%29%3D0%5C%5C%5C%5C%28x%2B2%29%28x%2B3%29%28x%2B4%29%3D0%5C%5C%5C%5Cx%3D-4%2C%20-3%2C%20-2)
You and add cause this sound like a problem where you add
Answer:
.735
Step-by-step explanation:
.735 is 98 percent of .75
Answer:
A
Step-by-step explanation:
Using the sine ratio in the right triangle
sin40° =
=
= ![\frac{AC}{7}](https://tex.z-dn.net/?f=%5Cfrac%7BAC%7D%7B7%7D)
Multiply both sides by 7, thus
AC = 7sin40° → A
Ans $0.15 cents per ounce wer: